Effect of exogenous Phytase on Egg Production and Egg Quality of Spent Hen (Bangladesh Journal of Livestock Research, 2020)
The present study determined, assessed and quantified the exogenous phytase on egg production and egg quality of spent hens. Ninety laying hens (ISA- Brown) received iso-energetic and iso-nitrogenous diet supplemented with 0, 0.05, 0.1, 0.15 and 0.2 % phytase and reared in cages. Each layer was fed 120g feed/day from 90 to 100 weeks of age. At the inception of the study the spent hen at the age of 90 weeks had an average egg production 65.21 %. Phytase addition in diet increased (p